Tingkat Kesabaran pada Guru Pendamping Anak Berkebutuhan Khusus di SDN-SN Pasar Lama 3 Banjarmasin - Rahmanita, Amalia; Hairina, Yulia; Musfichin, Musfichin (Jurnal Al-Husna, 2023)
The accompanying teacher plays a very important role. The difficulties experienced by accompanying teachers are many and serious. The accompanying teacher will face challenges and will be asked to put more effort and patience in helping children with special needs. This study refers to the patient aspect based on Subandi's theory, namely self-control, steadfastness, persistence, accepting the harsh reality with sincerity and gratitude, and a calm attitude. This research approach is quantitative with descriptive research type. This study examined 38 subjects of teachers accompanying children with special needs at SDN-SN Pasar Lama 3 Banjarmasin. The method used in this study is a Likert scale. The results of this study indicate that the level of patience of teachers accompanying children with special needs is generally in the moderate category with a percentage of 42% and is quite good or moderate with a value (mean) of 121.87 at intervals of 119<X≤125. The highest aspect is the aspect of self-control with a value (mean) of 57.32. and the lowest aspect is the aspect of calm attitude with a value (mean) of 13.5. So they can be patient with what they are going through. This is due to the belief that he values ​​his life. Keywords: children with special needs; special assistant teacher; patience; SDN-SN Pasar Lama 3 Banjarmasin.